Cardiovascular program to improve physical fitness in those over 60 years old – pilot study - Castillo-Rodríguez A (Dove Medical Press, 2014)
Alfonso Castillo-Rodríguez,1 José Luis Chinchilla-Minguet2 1Faculty of Sport, University of Pablo de Olavide, Seville, 2Department of Didactics of Musical, Plastic, and Corporal Expression, University of Malaga, Malaga, Spain Background: In Spain, more than 50% of 60-year-olds are obese. Obesity is a disease with serious cardiovascular risks. The mortality rate for cardiovascular disease in Spain is 31.1%.Objectives: To improve aerobic fitness, strength, flexibility and balance, and body composition (BC) in persons over 60 years old.Materials and methods: A clinical intervention study of 24 participants was carried out over a period of 3 months. Aerobic fitness was assessed using the Rockport 1-Mile Walk Test. Upper-body strength was evaluated with an ad hoc test. Flexibility and balance were evaluated using the Sit and Reach Test and the Stork Balance Stand Test, respectively. Anthropometric measurements were taken by bioelectrical impedance.Results: After 3 months of training, aerobic fitness was improved, as demonstrated by improved test times (pretest 13.04 minutes, posttest 12.13 minutes; P<0.05). Body composition was also improved, but the results were not statistically significant (fat mass pretest 31.58%±5.65%, posttest 30.65%±6.31%; skeletal muscle mass pretest 43.99±9.53 kg, posttest 46.63±10.90 kg).Conclusion: Our data show that in subjects over 60 years old, aerobic fitness was improved due to program intervention. However, these results should be treated with caution, because of the limited sample size and the brief time period of this pilot study. A more rigorous study would include a sample of at least 100 participants. Keywords: Rockport 1-Mile Walk Test, IPAQ, Sit and Reach Test, Stork Balance Stand Test, bioelectrical impedance and strength